Taxonomic revision and natural history of Metaphotina Piza, 1964 (Mantodea, Acontistidae) - Ferraz, Bernardo R.; Queiroga, Drielly; Souza-Dias, Pedro G. B.; Rivera, Julio (Zootaxa, 2025)
The genus Metaphotina Piza, 1964 is revised based on comparative morphology. Three species are recognized: Metaphotina bimaculata (Saussure, 1870), Metaphotina austri Ferraz, Souza-Dias & Rivera, 2023, and a newly described species from Bahia, Brazil, Metaphotina akaraje sp. nov. Three new synonyms of M. bimaculata are established after a detailed analysis of primary type specimens and their taxonomic and nomenclatural history: Acontista brevipennis Saussure, 1872 syn. nov., Acontista rehni Giglio-Tos, 1927 syn. nov., and Metaphotina piracicabensis Piza, 1964 syn. nov. The analysis of distributional records confirm that Metaphotina is associated with semiarid environments across the eastern South American Dry Diagonal, mainly encompassing the Cerrado, Caatinga, and Chaco biomes. Field observations enabled the identification of the egg cases, discovering the ability of females to produce parthenogenetic offspring, and the recognition and formal description of the myrmecomorphic protonymph of M. bimaculata. Notably, we report on nymphs of M. bimaculata feeding on extrafloral nectaries (EFNs), marking the first known instance of praying mantises interacting with these plant structures. A dichotomous key, extensive graphic documentation of intra- and interspecific variation, and distribution maps are provided to facilitate the identification of Metaphotina spp..